Analysis of the Role of the Halal Product Assurance Organizing Agency (BPJPH) in Increasing the Effectiveness of Supervision of Halal Product Certification and Labeling in Indonesia - Anisa Putri; Shabahah El Rojana; Angga Maulana Firmansyah; Muhammad Ersya Faraby (Penerbit Hellow Pustaka, 2025)
Indonesia, as the world's largest Muslim-majority country, faces significant challenges and significant opportunities in distributing halal-certified goods. Demand for halal products is not only a religious obligation but also a consumer protection measure encompassing health, safety, and morality. Therefore, implementing a halal product assurance system is vital to ensuring the fulfillment of Muslim consumers' rights amidst the rapidly evolving and increasingly diverse product market.